A well-informed ‘model of administration’ for agrarian states. Or: how not to fall into the trap of ‘nostri cation’ when comparing colonial West African States with 18th century Prussia - Treiber, Hubert (SocietàMutamentoPolitica, 2016)
In a noteworthy essay entitled “The Operation Called Vergleichen (Comparison)” Joachim Matthes has drawn attention to the fact that studies which claim to compare particular phenomena from one’s own culture (such as law or administration, for example) with those of an alien culture do not, strictly speaking, perform a real comparison. Instead, what takes place is (in his words) a “nostrification”, that is, “an appropriation of the other in one’s own terms” or conceptual assimilation. Even the ideal-type constructions of Max Weber seem largely to confirm this proposition. In principle, then, it ought to be quite hard to find studies which are not exposed to the charge of nostrification. In what follows works by Gerd Spittler are examined in some detail from this particular perspective. In the first instance Spittler investigated the specific problems encountered by the colonial administration in West African peasant states (1919-39), before examining if this problematic could be applied to the peasant state of Prussia in the 18th century. So, for example, he asked himself how a bureaucratic administration reliant on written documents resolved the problem of raising taxes on a body of untruly peasants who to a large extent communicated orally amongst themselves. Since in both cases Spittler relates the typical structures of an agrarian society to typical administrative structures, he attains a level of reflection where the ‘“One” can be translated into the “Other” and vice versa’ (Matthes), and in this way he escapes the particular danger of nostrification.